PEMANFAATAN WORD PRESS SEBAGAI PLATFORM PENGELOLAAN KONTEN DIGITAL WEBSITE DI SDIT NURUL HIKMAH PENAJAM PASER UTARA - Dinda Ruszayanthi; Arbiyah Herlinawati; Ramadiani, S.Pd., M.Si., M.Kom., Ph.D. (STKIP Subang, 2025)
WordPress is a content management system (CMS) widely used worldwide for creating and managing websites. This article aims to examine the use of WordPress in the context of creating personal, institutional, and small business websites. With its ease of use, plugin flexibility, and extensive community, WordPress is a top choice for users without a strong technical background. This research uses a qualitative descriptive approach with a literature review of various relevant sources, including journal articles, books, and WordPress.org documentation.